우리나라 경기변동의 안정성 분석: 서비스산업의 역할을 중심으로 - 이재준 (12006, 2011)
This study discusses the phenomenon behind various forms of macroeconomic volatility faced by countries in terms of industrial structure through empirical analysis, and in the process attempts to validate the role of the service industry. The analysis sho